2023
DOI: 10.7759/cureus.34833
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Spiritual Music on Heart Rate Variability in Medical Students: A Single-Group Experimental Study

Abstract: Background: There are ancient texts and modern studies alluding to the therapeutic benefits obtained from listening to music. Studies have shown that chanting "OM" has a relaxing effect by causing parasympathetic dominance, limbic deactivation, and decreasing the brain's dopamine levels. This research aims to study the effect of listening to OM chanting on the cardiovascular system and heart rate variability and its possible use as a stress buster among medical students.Materials and Methods: Fifty medical und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Articles were also excluded if the use of music described was prospective rather than retrospective 38,39 ; if they described an opportunity for medical students to design and submit creative works without discussion of musical artworks created by medical students [40][41][42][43] ; or if the use of music was incidental in the service of another artform such as theatre, 44,45 video, [46][47][48] vodcast 49 or identity text. 50 Finally, articles were excluded if they described musical activities with a cohort of medical students not directly related to general medical education, for example, qualitative explorations of musical experiences in which medical students have been participants, 51 studies testing a hypothesis about the effects of music with a cohort of medical students under experimental conditions, [52][53][54][55][56][57][58][59][60][61][62] Research orientation, 64 methodology and limitations were identified through an appraisal of research quality using JBI Critical Appraisal checklists, [65][66][67][68] with each study rated independently by two authors and discussed until agreement was reached by the group.…”
Section: Methodsmentioning
confidence: 99%
“…Articles were also excluded if the use of music described was prospective rather than retrospective 38,39 ; if they described an opportunity for medical students to design and submit creative works without discussion of musical artworks created by medical students [40][41][42][43] ; or if the use of music was incidental in the service of another artform such as theatre, 44,45 video, [46][47][48] vodcast 49 or identity text. 50 Finally, articles were excluded if they described musical activities with a cohort of medical students not directly related to general medical education, for example, qualitative explorations of musical experiences in which medical students have been participants, 51 studies testing a hypothesis about the effects of music with a cohort of medical students under experimental conditions, [52][53][54][55][56][57][58][59][60][61][62] Research orientation, 64 methodology and limitations were identified through an appraisal of research quality using JBI Critical Appraisal checklists, [65][66][67][68] with each study rated independently by two authors and discussed until agreement was reached by the group.…”
Section: Methodsmentioning
confidence: 99%